2015
DOI: 10.5090/kjtcs.2015.48.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Approach for Redo Mitral Valve Replacement: No Aortic Cross-Clamping and No Cardioplegia

Abstract: A 75-year-old woman who had previously undergone a double valve replacement was admitted to Asan Medical Center because of severe bioprosthetic mitral valve dysfunction and tricuspid regurgitation. Under hypothermic fibrillatory arrest without aortic cross-clamping, minimally invasive mitral and tricuspid valve surgery was performed via a right minithoracotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…[ 11 ] A recent study demonstrated that for patients who needed a second surgery for mitral valve replacement with a history of mitral valvuloplasty through a conventional incision or coronary artery bypass grafting, MI surgery through a right side of the chest incision was a good choice. [ 12 ] One patient received mitral valvuloplasty in our hospital 10 years ago and was admitted to the hospital again because of severe mitral valve stenosis; this patient recovered after MIMVR. Unlike in a traditional surgery with a large drainage volume and slow recovery, the endotracheal tube was removed on the first day after the operation, with a total drainage volume of 560 mL before the tube was removed.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] A recent study demonstrated that for patients who needed a second surgery for mitral valve replacement with a history of mitral valvuloplasty through a conventional incision or coronary artery bypass grafting, MI surgery through a right side of the chest incision was a good choice. [ 12 ] One patient received mitral valvuloplasty in our hospital 10 years ago and was admitted to the hospital again because of severe mitral valve stenosis; this patient recovered after MIMVR. Unlike in a traditional surgery with a large drainage volume and slow recovery, the endotracheal tube was removed on the first day after the operation, with a total drainage volume of 560 mL before the tube was removed.…”
Section: Discussionmentioning
confidence: 99%
“…Against the situation mentioned above, minimally invasive beating heart technique for redo mitral valve surgery in patients with giant left ventricle has emerged in this environment. More and more reports had confirmed that minimally invasive beating heart technique for redo cardic surgery could be safely performed successfully [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Resternotomy may also be complicated in patients who had chest radiotherapy or previous sternal wound infections or in patients with vascular structures (ascending aorta, brachiocephalic vein,right ventricle and bypass vessels) that lie directly behind the sternum. Recently minimally invasive beating heart technique for redo cardic surgery had been safely performed successfully [1][2][3][4][5][6][7], which combined the availability and the advantage of a right-sided minithoracotomy approach without resternotomy and beating heart technique without aortic cross-clamping and cardiac arrest. The beating heart technique can interfere with the mechanisms of ischemia-reperfusion injury [8,9] that may be advantageous particularly in patients with poor left ventricular functions [10][11][12][13][14].…”
mentioning
confidence: 99%
“…Resternotomy may also be complicated in patients who had chest radiotherapy or previous sternal wound infections or in patients with vascular structures (ascending aorta, brachiocephalic vein, right ventricle and bypass vessels) that lie directly behind the sternum. Recently minimally invasive beating heart technique for redo cardic surgery had been safely performed successfully [1][2][3][4][5][6][7], which combined the availability and the advantage of a right-sided minithoracotomy approach without resternotomy and beating heart technique without aortic cross-clamping and cardiac arrest. The beating heart technique can interfere with the mechanisms of ischemia-reperfusion injury [8,9] that may be advantageous particularly in patients with poor left ventricular functions [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%